Race and support for police use of force: findings from the UK. (9th August 2022) - Yesberg, Julia A.; Kyprianides, Arabella; Bradford, Ben; Milani, Jenna; Quinton, Paul; Clark-Darby, Oliver
ABSTRACT: The use of force is arguably the defining feature of police. Yet this power is often controversial: a key node in the contest and debate that almost always swirls around police, with the question of race never far from such contestation. In this paper, we consider the influence of race in responses to use of force incidents among British-based samples. Using two text-based vignette experiments and one video study, our aims are threefold: (1) to explore the influence of suspect race in how people respond to police use of force; (2) to test the interaction between participant ethnicity and suspect race; and (3) to understand what attitudes and beliefs influence how people respond to police use of force. We found no effect of suspect race on how people judged police use of force. White participants were slightly more accepting of police use of force than black participants, but there was no interaction with suspect race. The strongest predictor of acceptance of police use of force was trust in police, and, controlling for other relevant predictors, racial prejudice was also a significant positive predictor of acceptance of use of force. To our knowledge this is the first study of its kind to be fielded in the UK.